Effect of baseline characteristics on response to proton pump inhibitors in patients with peptic ulcer bleeding. Issue 2 (19th April 2017) - Lau, James; Lind, Tore; Persson, Tore; Eklund, Stefan
Abstract : OBJECTIVE : The rate of rebleeding from peptic ulcers could differ between Asian and Western populations. This study aimed to determine whether the observed twofold difference in rebleeding rates in two similarly designed clinical trials (one in Hong Kong [ n = 240], the other in a predominantly Western population [ n = 764, ClinicalTrials.gov identifier: NCT00251979]) can be explained by differences in baseline patient characteristics. METHODS : Two‐factor and multifactor analyses (adjusted by demographics, established risk factors for peptic ulcer and peptic ulcer bleeding, and disease severity variables) were performed using pooled data from the two studies. Cox regression analysis was used to predict the rebleeding risk at 3 days. RESULTS : In the two‐factor analysis (placebo vs esomeprazole/omeprazole and Western study vs Hong Kong study), data trended towards a reduced risk of rebleeding in the Western study (hazard ratio [HR] 0.69, 95% confidence interval [CI] 0.44–1.07, P = 0.094). The risk of rebleeding was similar in both studies after adjusted for multiple factors (HR 1.10, 95% CI 0.60–1.99, P = 0.767). The strongest predictor of rebleeding (apart from study drug) was a classification of American Society of Anesthesiologists (ASA) grade IV (HR 4.15, 95% CI 1.49–11.56, P = 0.006). When such patients were excluded, the difference in rebleeding rates between the studies reduced. CONCLUSION : The difference in rebleeding rates between the two studies is explained by the factors in our analysis, most importantly a classification of ASA grade IV, suggesting that other differences, including ethnicity, did not influence the rebleeding rate.